IMPLEMENTASI APLIKASI TIMAH APPROVAL PAYMENT (TAP) PADA PT. TIMAH TBK (STUDI KASUS PENGELUARAN KAS ATAS BIAYA PERJALANAN DINAS) - Sulisyana; Tri Setyo Mulyani, Hendarti; Medinal (Jurnal Akuntansi Bisnis Dan Keuangan, 2022)
Science and technology that are developing more and more advanced become an important requirement for companies in maintaining the continuity of company activities and business development. Recording all company activities is very important to be processed into information and make it easier for management to make decisions. PT. Timah Tbk as a State-Owned Enterprise based in Pangkalpinang City, Bangka Belitung Islands Province, has main business activities and various supporting businesses through subsidiaries spread across the territory of the Republic of Indonesia and abroad. To support the smooth running of business activities, it is necessary to assign employees to places of work or business outside the city of Pangkalpinang. Assignment of employees requires a Business Travel Letter. The process of making Official Travel Letters to paying for employee needs during business trips feels slow because it uses the traditional system. This study aims to analyze the problems that often occur in the process of making Official Travel Letters to the payment. With the discovery of these problems, the authors compare the traditional process with the process using the TAP (Timah Approval Payment) application. After conducting research, it was found that it was easy and smooth in making official travel letters to payments and recording in the general ledger